2021
DOI: 10.1097/hjh.0000000000002990
|View full text |Cite
|
Sign up to set email alerts
|

The mineralocorticoid receptor blocker spironolactone lowers plasma interferon-γ and interleukin-6 in patients with type 2 diabetes and treatment-resistant hypertension

Abstract: Background: The mineralocorticoid receptor antagonist spironolactone lowers blood pressure in patients with resistant hypertension despite antihypertensive treatment with angiotensin-converting inhibitors (ACEi) and angiotensin-II receptor blockers (ARB). In preclinical studies, spironolactone suppresses pro-hypertensive interleukin 17A (IL-17A).Objectives: Plasma samples were analysed from a randomized, double-blind placebo-controlled trial with spironolactone given to patients with type 2 diabetes mellitus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Thangaraj et al studied the immunomodulatory effects of the MR antagonist spironolactone on 119 type 2 diabetic patients with hypertension despite ongoing treatment with three or more antihypertensive drugs [ 33 ▪ ]. Administration of 25 mg of spironolactone per day to the patients resulted in significantly reduced serum T cell IFNγ -but not interleukin (IL)-17A-production that correlated with significantly reduced systolic blood pressure in the recipients [ 33 ▪ ].…”
Section: Recent Updates: Clinical Evidence Of the Role Of Interferon ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Thangaraj et al studied the immunomodulatory effects of the MR antagonist spironolactone on 119 type 2 diabetic patients with hypertension despite ongoing treatment with three or more antihypertensive drugs [ 33 ▪ ]. Administration of 25 mg of spironolactone per day to the patients resulted in significantly reduced serum T cell IFNγ -but not interleukin (IL)-17A-production that correlated with significantly reduced systolic blood pressure in the recipients [ 33 ▪ ].…”
Section: Recent Updates: Clinical Evidence Of the Role Of Interferon ...mentioning
confidence: 99%
“…Thangaraj et al studied the immunomodulatory effects of the MR antagonist spironolactone on 119 type 2 diabetic patients with hypertension despite ongoing treatment with three or more antihypertensive drugs [ 33 ▪ ]. Administration of 25 mg of spironolactone per day to the patients resulted in significantly reduced serum T cell IFNγ -but not interleukin (IL)-17A-production that correlated with significantly reduced systolic blood pressure in the recipients [ 33 ▪ ]. This double-blind placebo-controlled study also found macrophage IL-6 production was significantly reduced after 50 mg/day spironolactone therapy; however, plasma IFNγ levels were not significantly reduced at this higher dose, complicating interpretation [ 33 ▪ ].…”
Section: Recent Updates: Clinical Evidence Of the Role Of Interferon ...mentioning
confidence: 99%
See 3 more Smart Citations